2022
DOI: 10.3390/jcdd9020033
|View full text |Cite
|
Sign up to set email alerts
|

ICD Outcome in Pediatric Cardiomyopathies

Abstract: Background: Pediatric patients with cardiomyopathies are at risk of malignant arrhythmias and sudden cardiac death (SCD). An ICD may prevent SCD. The aim of this study was to evaluate ICD implantation outcomes, and to compare transvenous and subcutaneous ICDs (S-ICDs) implanted in pediatric patients with cardiomyopathies. Methods: The study is single center and retrospective, and includes pediatric patients with cardiomyopathies who required ICD implantation (2010–2021). Outcomes were recorded for appropriate/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Few studies compared the outcomes of S-ICD and transvenous ICD. There were no significant differences in the efficacy of both systems [128], while S-ICD showed less frequent lead-related complications and inappropriate shocks and more frequent pocket-related complications [129].…”
Section: Discussionmentioning
confidence: 86%
“…Few studies compared the outcomes of S-ICD and transvenous ICD. There were no significant differences in the efficacy of both systems [128], while S-ICD showed less frequent lead-related complications and inappropriate shocks and more frequent pocket-related complications [129].…”
Section: Discussionmentioning
confidence: 86%
“…A total of five studies [6][7][8][9][10] were identified (Supplementary Figure S2) including 236 patients (Group S-ICD: 76 patients; Group TV-ICD: 160 patients); 53.8% (n = 127) of them were males with an average age of 15.2 ± 6.5 years and weight of 64.6 ± 33.9 kg (Table 1). Overall, 58% (n = 137) of patients were implanted for primary prevention of SCD and the most frequent underlying diagnoses were hypertrophic cardiomyopathy (38.1%), channelopathies (25.9%), dilated cardiomyopathy (14%), idiopathic ventricular fibrillation (10.2%), and arrhythmogenic cardiomyopathy (10.2%) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Dual-chamber ICDs do not demonstrate superiority over single-chamber ICDs in discriminating supraventricular or sinus tachycardia. Lead failure issues are more prevalent in non-transvenous systems compared to transvenous systems, and the simplest ICD systems are associated with the lowest likelihood of lead-related complications [69,148,163].…”
Section: Prevention Of Scdmentioning
confidence: 99%